Densification studies of silicon carbide-based ceramics with yttria, silica and alumina as sintering additives - J. Marchi; J.C. Bressiani; A.H.A. Bressiani (Materials Research, 2001)
Silicon carbide has been extensively used in structural applications, especially at high temperatures. In this work, Y2O3, Al2O3 and SiO2 were added to beta-SiC in order to obtain highly dense ceramics. Sintering was conducted in a dilatometer and in a graphite resistance furnace and the densification behaviour was studied. Sintered samples were characterised by density measurements, the crystalline phases were identified by X-ray diffraction. Microstructural observation of polished and polished/etched samples was carried out with help of scanning electron microscopy. Silicon carbide ceramics with more than 90% of the theoretical density were obtained by pressureless sintering if a suitable proportion of the additives is used.